(NlEKCII gANSA fON b@LOWAs (NMONOGRAFIQ(B. (Nu^EBNOE POSOBIEs - (NtEODOR pFEJFERs; (Na(B.(Nn(B.(NbUHOWCEWs (NPEREWOD^IKs ((NsANKT(B-(NpETERBURGs (NlANXs (NpLANETA MUZYKIs, 2022)
(NgANS gWIDO FON b@LOW (B- (NNEMECKIJ PIANIST(B, (NPEDAGOG(B, (NDIRIVER I KOMPOZITOR(B.s
Keywords: (NMONOGRAFIQs